THE NATURE OF DIFFRACTION EFFECTS FROM ILLITE AND ILLITE-SMECTITE CONSISTING OF INTERSTRATIFIED TRANS-VACANT AND CIS-VACANT 2:1 LAYERS: A SEMIQUANTITATIVE TECHNIQUE FOR DETERMINATION OF LAYER-TYPE CONTENT - Drits V.A.; McCarty D.K. (My University, 1996)
Previous work has described the structural and diffraction criteria for distinguishing between tv-1M, cv-1M, and m-1M illite varieties, where tv-1M illite corresponds to a structure with trans vacant (tv) 2:1 layers, cv-1M illite consists of cis-vacant (cv) 2:1 layers, and m-1M illites consist of 2:1 layers with random distributions of octahedral cations over trans and cis sites within each layer. Detailed analysis of calculated and experimental X-ray diffraction (XRD) patterns from illites and mixed-layered illite-smectites (I/S) with a range of cis- and trans-vacant layer interstratification, and consideration of unit-cell parameters for pure tv-1M and cv-1M, provides insight into the nature of the diffraction effects from the interlayered structures with different types and contents of rotational stacking defects. Structural fragments of the 2M 1 and 2M 2 polytypes exist within 1Md structures in which rotational disorder is dominated by n·120 and n·60°, respectively. Such structural fragments constitute coherent-scattering domains and affect the peak positions of the diagnostic 11/reflections for rotationally disordered I/S and illites in different ways depending on the proportion of cis- and trans-vacant 2:1 layers. Simple techniques that do not require computer programs were developed for the semi-quantitative determination of the proportion of tv and cv 2:1 layers in I/S and illites where such layers are interstratified. These techniques may help to reveal the diversity of I/S and illite samples relating to the conditions of their formation and transformation.